1997
DOI: 10.1557/jmr.1997.0254
|View full text |Cite
|
Sign up to set email alerts
|

Development of preferred orientation in polycrystalline AlN thin films deposited by rf sputtering system at low temperature

Abstract: The development of preferred orientation in AlN thin films deposited on silica glass substrates by rf sputtering at low substrate temperature (<150 °C) has been studied. The main factors controlling the preferential orientation of the AlN thin films are the ion-bombardment energies, incidence angle of the arriving particles, and deposition rate. At low pressure, a perpendicular and highly directional energetic ion-bombardment induces an orientation of the crystallites with their c-axis perpendicular to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 18 publications
0
31
0
Order By: Relevance
“…The texture of samples deposited at 0.66 Pa is independent of the power applied to the target, as the small change observed in the texture parameter is statistically not significant. At a pressure of 1.33 Pa the (002) preferred orientation is significantly better at a power of 100 W as compared with samples deposited at 200 W. Lowering the power applied to the target decreases the deposition rate, a condition that promotes the growth of grains with (002) preferred orientation [6]. At 0.66 Pa, physical parameters that are pressure dependent, discussed in the following paragraph, will control the preferred orientation, overshadowing the effects of the power applied to the target.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…The texture of samples deposited at 0.66 Pa is independent of the power applied to the target, as the small change observed in the texture parameter is statistically not significant. At a pressure of 1.33 Pa the (002) preferred orientation is significantly better at a power of 100 W as compared with samples deposited at 200 W. Lowering the power applied to the target decreases the deposition rate, a condition that promotes the growth of grains with (002) preferred orientation [6]. At 0.66 Pa, physical parameters that are pressure dependent, discussed in the following paragraph, will control the preferred orientation, overshadowing the effects of the power applied to the target.…”
Section: Resultsmentioning
confidence: 98%
“…In addition, AlN thin films with preferred orientation are potential candidates for the piezoelectric material in surface acoustic wave devices due to its high sound velocity, high resistivity, and high breakdown voltage [1]. AlN thin films have been synthesized by several methods including chemical vapor deposition [2], plasma assisted molecular beam epitaxy [3], laser ablation deposition [4], electron cyclotron resonance [5], and ion beam assisted deposition [6]. Most of these techniques require a substrate with a specific orientation (sapphire or SiC) and a high deposition temperature (1000 -C) in order to obtain the best crystallinity and texture in the deposited film.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A. Rodríguez-Navarro et al [19] found that for low deposition rate conditions the preferred orientation is after (001) while for higher deposition rates the (101) orientation is observed. Ion bombardment processes greatly…”
Section: Structure and Microstructure Of The Coatingsmentioning
confidence: 99%
“…In spite of the use of glancing mode, the fact that different intensities were found in the samples, with and without gold, suggests that preferential orientations could be related either with the different Al/N ratios or to possible influences of Au incorporation in the adatom mobility of the arriving species to the growing film [16,18,19,20]. In fact, the presence of Au atoms during the film growth stage has most probably interfered with the incorporation of Al-N clusters in the film (as discussed before).…”
Section: Structure and Microstructure Of The Coatingsmentioning
confidence: 99%